Disposable Voltammetric Immunosensor for Determination and Quantification of Biomarker CA 15-3 in Biological Specimens - Ana Elisa F. Oliveira; Arnaldo César Pereira; Mayra A. C. Resende; Lucas Franco Ferreira (Analytica, 2024)
A disposable voltammetric immunosensor was developed to measure breast cancer biomarker 15-3 (CA 15-3) in human saliva and serum samples. Screen-printed paper-based electrodes (f-SPE) previously fabricated by our research group using homemade conductive inks were used as transducers, which were later modified only with gold nanoparticles to immobilize anti-CA 15-3 antibodies. The sensor was operated using antigen–antibody interactions in conjunction with a redox species (ferrocyanide potassium) for the indirect determination of the CA 15-3 antigen. The device characterization involved atomic force microscopy (AFM) and electrochemical analysis. Optimization of the construction and response of the immunosensor was achieved at incubation times of 6 h for anti-CA 15-3, 1 h for bovine serum albumin, and 1 h for interaction with CA 15-3. The sensor displays a linear range between 2 and 16 U/mL, with a sensitivity of 0.012 μA/U mL−1, a limit of detection (LOD) of 0.56 U/mL, and a limit of quantification (LOQ) of 1.88 U/mL. The interfering substances minimally affected the signal, with 4.94% response variation, and the reproducibility of the immunosensor demonstrated a relative standard deviation (RSD) of 5.65%. The sensor successfully determined the CA 15-3 concentration in human serum and saliva, demonstrating its potential for clinical analysis.